Un destin foudroye?: Un footballeur dans l’enfer du terrorisme: By Kodjovi Obilale?. Paris: Talent Sport, 2015 - Agbedahin, Komlan (Acta Academica: Critical views on society, culture and politics, 2018)
Un destin foudroye?: Un footballeur dans l’enfer du terrorisme, written by Kodjovi Obilale?, is a 10-chapter autobiography, the story of the unique professional football journey of a West African child who became the centre of attraction in the aftermath of a terrorist attack.